The time difference between dental calculator calculation and manual calculation in Geriatric Oral Health Assessment Index: Perbedaan waktu antara perhitungan menggunakan kalkulator gigi dan perhitungan manual pada Geriatric Oral Health Assessment Index - Erthasya Aura Abrialihan; Yulia Rahmad; Utmi Arma; Ricky Amran; Valendriyani Ningrum (Makassar Dental Journal, 2026)
Conventionally, manual measurement of the Geriatric Oral Health Assessment Index (GOHAI) is time-consuming and prone to error. To address this chal-lenge, a dental calculator application was developed as a digital technology-based solution to speed up GOHAI calculations. This study determined the dura-tion of manual GOHAI measurement compared to the use of a digital dental calculator application. This was a quasi-experimental study with a posttest-only group design. Convenience sampling was used, resulting in a total of 70 samples from the population of students at the Faculty of Dentistry, Baiturrah-mah University, who met the inclusion and exclusion criteria. The data collection process consisted of manual measurements taken in the first week and di-gital measurements taken in the third week. It was found that the average GOHAI measurement time using the digital dental calculator application (36.28 se-conds) was faster than using paper and pen (88.78 seconds) with a p-value of 0.000 (p<0.05), indicating a significant difference. The average difference in GOHAI measurement time between the manual and digital methods was 52.5 seconds. It was concluded that there was a difference in time between the use of a digital dental calculator and a manual application for GOHAI measurement.